Potassium Levels, Antioxidant Activity, and Acceptability of Yellow Velvetleaf (Limnocharis flava (L.) Buchenau.) Snack Bar - Agnes Boenardy; Handayani, Septy (Universitas Airlangga, 2025)
Snack food consumption are high in fat and sodium, contributing to the risk of hypertension. One potential solution to this issue is to transform snacks into a more nutritionally superior form, such as snack bars. Previous studies did not thoroughly explore the potassium content of yellow velvetleaf as a potential product for addressing hypertension. This study aimed to investigate the differences in potassium content antioxidant activity and acceptability in snack bars with the addition of yellow velvetleaf flour. This research adopted a true experimental design. The gravimetric method was employed to determine potassium content, while the DPPH method was used to assess antioxidant activity. Statistical analysis of the average potassium content and antioxidant activity revealed significant differences among snack bars with 0%, 5%, 10%, and 15% added yellow velvetleaf flour. The highest average potassium content, 325.67 mg, was observed in the 15% treatment, while the maximum average antioxidant activity reached 21.7%. Considering the acceptability of the snack bars based on liking tests and statistical analysis, the treatment with 10% added yellow velvetleaf flour emerged as the most preferred in terms of taste and texture. The incorporation of yellow velvetleaf flour into snack bars not only increased potassium levels and antioxidant activity but also influenced overall acceptability. Conclusion of this research is the optimal formulation for the yellow velvetleaf snack bar is X2, because of containing a higher acceptance level and contains potassium which could serve as a viable solution to enhance potassium intake following current dietary habits.